2019
DOI: 10.1177/1708538119836005
|View full text |Cite
|
Sign up to set email alerts
|

External validation of CLI Frailty Index and assessment of predictive value of modified CLI Frailty Index for patients with critical limb ischemia undergoing infrainguinal revascularization

Abstract: Objectives CLI Frailty is a useful diagnostic criterion of frailty in patients with critical limb ischemia (CLI). It is important to evaluate not only comorbidities but also frailty in decision making to select the type of treatment for CLI patients. The purposes of our study were to externally validate the CLI Frailty Index and to evaluate the modified CLI Frailty Index by measurement of skeletal muscle mass using computed tomography. Methods Patients who underwent preoperative computed tomography examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…These conflicting findings could be explained by disparities in disease severity. Indeed, the alterations in mitochondrial oxidative capacity may have been the result of factors associated with higher morbidity in PAD, such as sarcopenia [33][34][35].…”
Section: Clinical Datamentioning
confidence: 99%
“…These conflicting findings could be explained by disparities in disease severity. Indeed, the alterations in mitochondrial oxidative capacity may have been the result of factors associated with higher morbidity in PAD, such as sarcopenia [33][34][35].…”
Section: Clinical Datamentioning
confidence: 99%
“…Indeed, in 2015, and subsequently in 2017, Matsubara et al reported that sarcopenia was associated with higher cardiovascular events and lower survival, in 64 and 114 patients suffering from CLI, respectively. 22,23 Recent papers confirmed this association in retrospective studies including patients with CLI, where low skeletal muscle mass was predictive of a worse overall survival [24][25][26] Figure 2).…”
Section: Resultsmentioning
confidence: 81%
“…Data extraction led to the evaluation of 140 publications, of which 87 met the inclusion criteria, and 79 were included in the final review. Of these, 18 gave sufficient data for epidemiological analysis and diagnostic criteria, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] 33 gave sufficient data for mechanistical analysis, and 28 gave sufficient data for therapeutic approaches. 1/Epidemiological data: Is sarcopenia a rare condition in patients with PAD?…”
Section: Resultsmentioning
confidence: 99%
“…8,10 Ongoing research may provide further useful information regarding assessment of frailty, physical function and cognitive impairment, as well as other outcomes such as quality of life and durability of revascularisation, in patients with CLTI. 34 Previous research has also demonstrated associations with frailty and outcomes over ≥1 year 3,4,[35][36][37] associated with worse overall survival and AFS at two-years, adjusting for tissue loss in their multivariable model. 3 Using the critical limb ischaemia (CLI) frailty index, a novel three-item frailty score, Morisaki et al (266 patients) showed an independent association of frailty with worse overall survival and AFS.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, their follow-up study (127 patients) showed only an independent association with overall survival, and the CLI frailty index is only validated to predict risk, not its ability to identify frailty. 10,35,36 Soon et al (233 patients) used the modified frailty index (mFI) and also found an association of frailty with worse one-year mortality but not major amputation in CLTI. 37 However, the utility of the mFI as a frailty tool has been questioned.…”
Section: Discussionmentioning
confidence: 99%